Evolution of South American Mammalian Predators During the Cenozoic: Paleobiogeographic and Paleoenvironmental Contingencies - Prevosti, Francisco J. (Springer Geology,, 2018)
This book summarizes the evolution of carnivorous mammals in the Cenozoic of South America. It presents paleontological information on the two main mammalian carnivorous groups in South America; Metatheria and Eutheria. The topics include the origin, systematics, phylogeny, paleoecology and evolution of the Sparassodonta and Carnivora. The book is based on a wide variety of published sources from the last few decades.